2018
DOI: 10.21138/bage.2571
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de distribución de la oferta turística mediante técnicas geoestadísticas en Extremadura (2004-2014)

Abstract: <p>El rápido incremento de la oferta de alojamientos en Extremadura no se ha visto correspondido con un aumento armónico en el número de visitantes y de pernoctaciones, hecho que ha provocado un desajuste notable entre la oferta y la demanda. El aumento de oferta se ha producido de forma desigual sobre el territorio, por lo que esta investigación pretende determinar los patrones de distribución que se detectan en los tres grandes grupos de oferta: hotelera, extrahotelera y rural, así como su evolución. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…In the specific case of the territory on which the present study focuses, a series of studies have been carried out with a common purpose: ascertaining the pattern of distribution in the region. As a common result of all of these it was found that tourist activities are not distributed at random in the territory; there are areas in which there is greater tourist intensity (Martín et al 2018;Sánchez Martín et al 2013;Sánchez-Rivero 2019, 2020;Sánchez-Martín et al 2019;Sánchez-Rivero 2008). To reach these conclusions, these studies used spatial association measures that allowed them to discover different clusters in which there is a greater tourist density.…”
Section: The Importance Of Space In Accommodation Distributionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the specific case of the territory on which the present study focuses, a series of studies have been carried out with a common purpose: ascertaining the pattern of distribution in the region. As a common result of all of these it was found that tourist activities are not distributed at random in the territory; there are areas in which there is greater tourist intensity (Martín et al 2018;Sánchez Martín et al 2013;Sánchez-Rivero 2019, 2020;Sánchez-Martín et al 2019;Sánchez-Rivero 2008). To reach these conclusions, these studies used spatial association measures that allowed them to discover different clusters in which there is a greater tourist density.…”
Section: The Importance Of Space In Accommodation Distributionmentioning
confidence: 98%
“…However, if there is a field in which efforts have been focused on creating knowledge on tourist activities and their distribution in a space, there is no doubt that this is the distribution of the tourist offering in the territory. To do this, some studies have focused on analyzing how accommodation companies are distributed in space, using the entity itself or the places offered by each of the existing establishments as a reference base (Martín et al 2018;Yang andWong 2012, 2013;Majewska 2015Majewska , 2017Li et al 2015;Xing-Zhu and Qun 2014;Almeida-García et al 2018;Balaguer and Pernías 2013;Sánchez Martín et al 2013;Sánchez-Rivero 2019, 2020;Batista e Silva et al 2018;Sánchez-Martín et al 2019;Sánchez-Rivero 2008;Sarrión-Gavilán et al 2015). The ultimate purpose of these studies is to identify groupings of accommodation establishments in a space, i.e., the identification of spatial clusters.…”
Section: The Importance Of Space In Accommodation Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Como consecuencia de la utilidad que posee el análisis locacional y las diferentes técnicas geoestadísticas en el contexto actual de big data, no han tardado en surgir estudios geográficos que aúnan sendos criterios a diferentes aplicaciones, ya sea para analizar los retos y oportunidades que presentan (Gutiérrez et al, 2016), o para obtener resultados sobre temas específicos (Sánchez et al, , 2018. Del mismo modo, ha surgido una nueva corriente en torno a la geográfia que multitud de autores definen como Neogeografía (Bosque, 2015), la cuál hace referencia a aquellos trabajos elaborados por actores que, sin conocimientos previos en la materia, crean su propia cartografía a través de la información disponible en la red (Turner, 2006).…”
unclassified